Arbitrary signals of trustworthiness – social judgments may rely on facial expressions even with experimentally manipulated valence. Issue 5 (May 2019) - Kocsor, Ferenc; Kozma, Luca; Neria, Adon L.; Jones, Daniel N.; Bereczkei, Tamas
Abstract: Generalization has been suggested as a basic mechanism in forming impressions about unfamiliar people. In this study, we investigated how social evaluations will be transferred to individual faces across contexts and to expressions across individuals. A total of 93 people (33 men, age: M = 29.95; SD = 13.74) were exposed to facial images which they had to evaluate. In the Association phase, we presented one individual with (1) a trustworthy, (2) an untrustworthy, (3) or an ambiguous expression, with either positive or negative descriptive sentence pairs. In the Evaluation phase participants were shown (1) a new individual with the same emotional facial expression as seen before, and (2) a neutral image of the previously presented individual. They were asked to judge the trustworthiness of each person. We found that the valence of the social description is transferred to both individuals and expressions. That is, the social evaluations (positive or negative) transferred between the images of two different individuals if they both displayed the same facial expression. The consistency between the facial expression and the description, however, had no effect on the evaluation of the same expression appearing on an unfamiliar face. Results suggest that in social evaluation of unfamiliar people invariant and dynamically changing facial traits are used to a similar extent and influence these judgements through the same associative process.